Kemampuan Gerak Dasar Lari Jarak Menengah Pada Siswa Sekolah Menengah Pertama - Laksana, Anak Agung Ngurah Putra; Adnyana, I Wayan; Jenaru, Kandidus Jimyanto (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2021)
This study aims to determine the basic movement ability of middle-distance running in junior high school students. The method of this research is descriptive qualitative which is carried out on students of class VIII A SMP Widya Sakti Denpasar. The sample in this study was 32 students from class VIII A. Data collection techniques used triangulation, namely observation, interviews, and questionnaires. Analysis of the data used is the analysis of Miles and Huberman, namely the analysis of interactive model data through the steps of data collection, data reduction, data presentation, and drawing conclusions. The results of the observations showed that there were students in the good category with the percentage of results as much as 50% (16 students) and the sufficient category with the percentage of the results of the observation scores as much as 50% (16 students). The results of the interview data show that the learning process has not been maximized due to inhibiting factors. The results of the questionnaire data showed as many as 12 students (37.5%) were in the good category and as many as 20 students (62.5%) were in the sufficient category. Based on the three sources of data, the results of the study indicate that the students' ability to perform the basic movements of middle-distance running is not yet maximal. This research can be used as a reference for teachers, coaches and sports activists in improving the ability to run basic movements, namely by coordinating physical conditions and infrastructure.